Design and Synthesis of Building Blocks for PPII‐Helix Secondary‐Structure Mimetics: A Stereoselective Entry to 4‐Substituted 5‐Vinylprolines. Issue 4 (19th December 2017) - Chiha, Slim; Soicke, Arne; Barone, Matthias; Müller, Matthias; Bruns, Judith; Opitz, Robert; Neudörfl, Jörg‐Martin; Kühne, Ronald; Schmalz, Hans‐Günther
Abstract : In the course of our studies towards the synthesis of proline‐based secondary‐structure mimetics, we developed a straightforward methodology for the diastereoselective preparation of 4‐alkyl‐5‐vinyl‐substituted proline derivatives. Starting from N ‐Boc‐protected tert ‐butyl pyroglutamate, α‐alkylation, lactam reduction and acid‐catalyzed methanolysis afforded 4‐alkyl‐5‐methoxyproline derivatives. After BF3 ‐induced formation of an N ‐acyl‐iminium intermediate, the introduction of the 5‐vinyl side chain was achieved with high diastereoselectivity by using vinylmagnesium bromide in the presence of AlCl3 or CuBr· SMe2 to afford either the cis ‐ or the trans ‐product, respectively. The utility of the method was demonstrated in the rapid and efficient construction of new diproline mimetics rigidified in a polyproline‐type II helix (PPII) conformation. Abstract : Starting from pyroglutamic acid, 4‐substituted‐5‐vinylprolines were stereoselectively prepared and used as building blocks for the synthesis of conformationally well‐defined diproline analogs, which are of interest as proline‐derived modules (ProMs) for the construction of PPII‐helix secondary‐structure mimetics acting as inhibitors of relevant protein‐protein interactions.